Characterization of intact mRNA-based therapeutics by charge detection mass spectrometry and mass photometry - Evolène Deslignière; Lauren F. Barnes; Thomas W. Powers; Olga V. Friese; Albert J.R. Heck (Molecular Therapy: Methods & Clinical Development)
The impressive success of mRNA-based vaccines to combat COVID-19 has encouraged biopharmaceutical companies to invest in broader applications of alike vaccines for various diseases. Analytical approaches must keep pace to support this surge in the development of mRNA-based therapies. Intact mass analysis of mid- to large mRNA molecules (>1,000 nt) poses significant analytical challenges due to mRNA size, heterogeneity, and instability. Here, we demonstrate how single-particle Orbitrap-based charge detection mass spectrometry (CDMS) and mass photometry (MP) approaches can rapidly measure the mass of various intact high-mass capped mRNAs, up to 9,400 nt (∼3 MDa) in size. While ensemble MS yielded approximate masses for mRNAs <2,000 nt, it failed to provide information on samples of longer sequences. The drawbacks of ensemble MS could be avoided by recording individual ions. Low-charge mRNA components showed unstable ion behavior, hampering initial CDMS measurements, whereas high-charge populations offered better signal-to-noise and reduced charge uncertainty, with drastically improved mass accuracy. Lastly, in-solution MP enabled the measurement of mRNAs with high accuracy, while revealing low amounts of mRNA fragments and dimers that are sometimes overlooked in CDMS. Overall, CDMS and MP provide complementary methods that enable the study of large heterogeneous mRNA without requiring prior digestion or online separation.